Diverging stories of “Missing Women” in South Asia: is son preference weakening in Bangladesh? - Kabeer N.; Huq, Lopita; Mahmud, Simeen (Routledge, 2016)
his article was published in The Journal of Feminist Economics [ © 2013 IAFFE. ] and the definite version is available at: 10.1080/13545701.2013.857423 The Article's website is at: http://www.tandfonline.com/doi/abs/10.1080/13545701.2013.857423